Isolation and purification of diterpenoids from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS. Issue 20 (18th October 2018) - Dai, Li-Ping; Zhang, Ling-Xia; Liu, Ya-Lin; Wu, Hong; Liu, Rui-Xin; Zhao, Meng; Tian, Shuang-Shuang; Jiang, Xue; Chen, Sui-Qing
Abstract: Cytotoxic diterpenoids were enriched and orientation prepared from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS. Four diterpenoids were obtained, including a novel compound: 1 α -acetoxy-7 α, 14 β, 20 α -trihydroxy- ent - kau r-16-en-15-one (1 ); together with three known compounds kamebakaurin (2 ), lasiokaurin (3 ), enmenol-1- β -glucoside (4 ). Their structures were elucidated on the basis of spectroscopic methods in conjunction with published data for their analogues. All compounds were tested for their cytotoxic effects against five human cancer cell lines HCT-116, HepG2, A2780, NCI-H1650 and BGC-823, respectively. Compounds1 and2 showed obviously cytotoxic activity against the five cancer cell lines with IC50 ranging from 1.06 to 3.60 μM. Compounds3 and4 showed selective cytotoxic activity. Abstract :